2009
DOI: 10.1186/1746-160x-5-20
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral versus bilateral thyroarytenoid Botulinum toxin injections in adductor spasmodic dysphonia: a prospective study

Abstract: ObjectivesIn this preliminary prospective study, we compared unilateral and bilateral thyroarytenoid muscle injections of Botulinum toxin (Dysport) in 31 patients with adductor spasmodic dysphonia, who had undergone more than 5 consecutive Dysport injections (either unilateral or bilateral) and had completed 5 concomitant self-rated efficacy and complication scores questionnaires related to the previous injections. We also developed a Neurophysiological Scoring (NPS) system which has utility in the treatment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 31 publications
0
28
0
1
Order By: Relevance
“…Effective therapeutic doses in different clinical conditions are much lower-in some conditions like spasmodic dysphonia in order of picograms (Upile et al, 2009). Main pharmacokinetic and pharmacodynamic factors which summate and result in high BoNT/A potency are summarized in sections 3.…”
Section: Toxicity and Clinical Potency Of Bont/amentioning
confidence: 99%
“…Effective therapeutic doses in different clinical conditions are much lower-in some conditions like spasmodic dysphonia in order of picograms (Upile et al, 2009). Main pharmacokinetic and pharmacodynamic factors which summate and result in high BoNT/A potency are summarized in sections 3.…”
Section: Toxicity and Clinical Potency Of Bont/amentioning
confidence: 99%
“…A large retrospective study of 901 patients demonstrated the safety and efficacy of Botox [30]. In a retrospective study of 31 patients who had undergone five consecutive Dysport injections for ADSD, unilateral injections to the thyroarytenoids were just as effective as bilateral injections in terms of voice improvement and duration of action, with no posttreatment total voice loss observed with unilateral injections [31,32]. BoNT-B (Myobloc) was found to be safe and effective for ADSD in a class IV single-site, open-label study in 13 patients [33].…”
Section: Oromandibular Dystonia and Spasmodic Dysphoniamentioning
confidence: 98%
“…Allgemein ist zu sagen, dass sich bezüglich erwünschter und unerwünschter Wirkungen keine Unterschiede zwischen uni- und bilateralen Injektionsschemata nachweisen lassen und intiale Heiserkeiten für wenige Tage bis Wochen bei endolaryngealen Behandlungen mit Botulinumtoxin nicht vermeidbar erscheinen [129][130][131][132][133][134][135][136]. Diese sind jedoch passager und werden bei überwiegend positivem Behandlungseffekt von den Patienten akzeptiert [5,124].…”
Section: Endolaryngeale Behandlungunclassified